STRATEGI AKSELERASI REFUSED DERRIVED FUEL KABUPATEN CILACAP SEBAGAI PENGGERAK EKONOMI SIRKULAR DI INDONESIA - Maghfuri, Ahamd; Wahyu Nugroho , Dwi (Jurnal Inovasi Daerah, 2024)
Waste management is an innovation that needs to be developed. With good management, waste will be transformed into a source of income. Waste management with a technological touch will result in optimal economic improvement. One of the efforts made is the utilization of Refused Derived Fuel (RDF) as an alternative energy source. In this context, waste management becomes very important not only as a technical issue but also as a key to unlocking new potential in a sustainable economy. The research method used in this study is qualitative, with data collection from literature review, field observation, and interviews. SWOT Analysis technique is carried out to formulate optimal strategies. The results of this study indicate that the acceleration of RDF in Cilacap Regency as a driver of the circular economy in Indonesia can be done by implementing the main strategies that have been formulated, namely the development of RDF in Integrated Waste Management Sites (TPST) by optimizing technology and local resources.